The astrophyllite supergroup: nomenclature and classification. (1st February 2017) - Sokolova, Elena; Cámara, Fernando; Hawthorne, Frank; Ciriotti, Marco
Here we report a nomenclature and classification for the astrophyllite-supergroup minerals. The HOH block is the main structural unit in all astrophyllite-supergroup structures; it consists of three H–O–H sheets where the T4O12 astrophyllite ribbons occur in the H sheets. In each structure, HOH blocks alternate with I (Intermediate) blocks along [001]. The twelve minerals of the astrophyllite supergroup are divided into three groups based on (1) the type of self-linkage of HOH blocks, i.e. (a) HOH blocks link directly where they share common vertices of D octahedra, or (b) HOH blocks do not link directly; and (2) the dominant cation of the O sheet (the C group: C7 apfu). In the astrophyllite group (HOH blocks connect via D– XPD–D bridges, Fe2+ is dominant at C7), there are six minerals: astrophyllite, niobophyllite, zircophyllite, tarbagataite, nalivkinite and bulgakite. In the kupletskite group (HOH blocks connect via D–XPD–D bridges, Mn2+ is dominant at C7), there are three minerals: kupletskite, niobokupletskite and kupletskite-(Cs). In the devitoite group (HOH blocks do not connect via D–XPD–D bridges), there are three minerals: devitoite, sveinbergeite and lobanovite. The general formula for the astrophyllite-supergroup minerals is of the form A2pBrC7D2(T4O12)2IXOD2XOA4XPDnWA2, where C [cations at the M(1–4) sites in the O sheet] = Fe2+, Mn, Na, Mg, Zn, Fe3+, Ca, Zr, Li; D (cations in the H sheets) = [6, 5]Ti, Nb, Zr, Sn4+, [5] Fe3+, Mg, Al; T = Si, minor Al; A2pBrIWA2 (I block) where p = 1, 2; r = 1, 2; A = K, Cs, Ba, H2O, Li, Rb, Pb2+, Na, ; B = Na, Ca, Ba, H2O, ; I represents the composition of the central part of the I block, excluding peripheral layers of the form A2pBrWA2, e.g. (PO4)2(CO3) (devitoite); XOD = O; XOA = OH, F; XPD = F, O, OH, H2O, , where n = 0, 1, 2 for (XPD) n; WA = H2O, .